1987
DOI: 10.1148/radiology.162.1.3786763
|View full text |Cite
|
Sign up to set email alerts
|

Albumin labeled with Gd-DTPA as an intravascular, blood pool-enhancing agent for MR imaging: biodistribution and imaging studies.

Abstract: Albumin is a macromolecule that remains largely confined to the vascular space after intravenous administration. Human serum albumin was paramagnetically labeled by covalently binding from nine to 18 gadolinium-DTPA (diethylenetriaminepentaacetic acid) chelates per protein molecule. This conjugate was tested in varying doses for in vivo biodistribution and effectiveness in tissue relaxation. After intravenous injection of the agent in rats, T1 relaxation times were significantly reduced in samples of the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(104 citation statements)
references
References 0 publications
3
101
0
Order By: Relevance
“…By comparison, the blood pool agent albumin(Gd-DTPA) 30 is largely retained in the intravascular space with a half-life of 88min after intravenous injection and can remain in the bloodtstream and extravascular compartment two weeks after injection. (77,78) These undesirably long retention times have precluded its use in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, the blood pool agent albumin(Gd-DTPA) 30 is largely retained in the intravascular space with a half-life of 88min after intravenous injection and can remain in the bloodtstream and extravascular compartment two weeks after injection. (77,78) These undesirably long retention times have precluded its use in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Albumin-(Gd-DTPA)30is a prototype MMCM with a molecular weight of 92 kDa and an initial distribution volume of 0.05 I/kg, which closely ap proximates the blood volume [16] …”
Section: Contrastmediamentioning
confidence: 99%
“…In addition, since Gd-DTPA relaxivity is also affected by magnetic field strength, temperature, and the macromolecule to which it is attached, direct comparison of our results with other studies is difficult. Schmiedl et al [32] reported a R 1 value for Gd-DTPA-Albumin (9 Gd-DTPA per albumin) to be 110 L/mmol-s measured at 0.25 T, 37 °C. Brasch [14] reported a R 1 value of 14.4 L/mmol-s per Gd for Albumin-Gd-DTPA at 0.25 T, 25 °C.…”
Section: Discussionmentioning
confidence: 99%